Fabrication of Photonic Microbricks via Crack Engineering of Colloidal Crystals. (13th December 2019) - Phillips, Katherine R.; Zhang, Cathy T.; Yang, Ting; Kay, Theresa; Gao, Chao; Brandt, Soeren; Liu, Lei; Yang, Haizhao; Li, Yaning; Aizenberg, Joanna; Li, Ling
Abstract: Evaporation‐induced self‐assembly of colloidal particles is one of the most versatile fabrication routes to obtain large‐area colloidal crystals; however, the formation of uncontrolled "drying cracks" due to gradual solvent evaporation represents a significant challenge of this process. While several methods are reported to minimize crack formation during evaporation‐induced colloidal assembly, here an approach is reported to take advantage of the crack formation as a patterning tool to fabricate microscopic photonic structures with controlled sizes and geometries. This is achieved through a mechanistic understanding of the fracture behavior of three different types of opal structures, namely, direct opals (colloidal crystals with no matrix material), compound opals (colloidal crystals with matrix material), and inverse opals (matrix material templated by a sacrificial colloidal crystal). This work explains why, while direct and inverse opals tend to fracture along the expected 111 planes, the compound opals exhibit a different cracking behavior along the nonclose‐packed 110 planes, which is facilitated by the formation of cleavage‐like fracture surfaces. The discovered principles are utilized to fabricate photonic microbricks by programming the crack initiation at specific locations and by guiding propagation along predefined orientations during the self‐assembly process, resulting in photonic microbricks with controlled sizes and geometries. Abstract : Rational engineering of crack formations in colloidal crystals is developed as a versatile route to fabricate photonic microstructures with controlled geometries and sizes. This strategy is based on a mechanistic understanding of the orientation‐dependent fracture behavior of colloidal crystals, which guides the design of patterned substrates with stress concentrators for controlled crack formation and propagation.